Unlocking Academic Excellence: The Impact of Implementing Arabic Language Learning on Student Achievement - Karim, Asad Abdul; Maksum, Muh. Nur Rachim; Mustofa, Triono Ali; Mubarok, Fahmi Ulum Al (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Language has a vital role for humans, namely, to express one's heart and thoughts to another. Arabic has a value of beauty that other languages do not-the Qur'an language, namely kalamullah. Arabic is essential for everyone to learn. However, it is difficult for students to understand Arabic because it is a foreign language. Students tend to be disinterested and perceive it as a scourge, causing low student learning outcomes. This is evident from the daily test scores of students below the KKM by more than 50% at MTsN 6 Boyolali. This study uses a qualitative approach. The research site is at MTsN 6 Boyolali. The sources of this research are Arabic teachers; the informants of this research are school principals and 7th-grade students. The data were obtained from interviews, observations and documentation. The validity of the data by using triangulation of sources and techniques. The data analysis technique uses an interactive model that includes data collection, reduction, presentation, and conclusion. The results showed that: (1) The application of Arabic language learning with 7th-grade students' unmu media at MTsN 6 Boyolali is going well, starting from planning, namely making lesson plans, syllabus, prota, promissory notes, KMM and making Unmu media. The implementation starts with preparing questions, explaining the material, forming groups, discussing, explaining the discussion results, responding, concluding and finally, the assessment. (2) The application of Arabic language learning with unmute media for 7th-grade students at MTsN 6 Boyolali can improve student achievement because students do daily tests with enthusiasm, and the results of daily tests show 78% of students get scores above the KKM and as many as 22% of students below KKM (KKM 75); this is proof that the application of unmu media can improve learning achievement.